Ethnomathematics for capacity building in mathematics education - Vistro-Yu, Catherine P (Archīum Ateneo, 2010)
The Mathematics Framework for Philippine Basic Education (MATHTED and SEI, in press), a document that aims to guide the development of curricular contents in mathematics, identifies cultural-rootedness as one of the cognitive values that mathematics education in the Philippines must inculcate. Cultural-rootedness is defined as ?appreciating the cultural value of mathematics and its origins in many cultures, its rich history and how it has grown and continues to evolve?. Ethnomathematics, described as the ?mathematics which is practiced among identifiable cultural groups, such as national tribal societies, labor groups, children of a certain age bracket, professional classes and so on? (D?Ambrosio, 1997, p.16), has rich potentials in increasing a country?s capacity to provide better mathematics education to its people. It is a vehicle for developing the value of cultural-rootedness thus recognizing and valuing the significant mathematical knowledge within the Philippines and how this mathematics has and continues to play a significant role in building capacity within the Philippines and its people. This paper provides examples of ?latent? mathematics that are found in various cultural groups in the Philippines. With these examples, the paper argues for changes in Philippine mathematics education to recognize and include Ethnomathematics encouraging teachers and communities to actively seek ways to include the non-traditional, non-Western mathematics in their teaching of mathematics in schools. These would include the different ways of counting, measuring, patterning, navigating, constructing, creating shapes, computing and other mathematical skills of various cultural groups. By this, Filipino students will learn to both appreciate the many cultures in the country and develop ways to include these cultures into the mainstream Philippine culture, thereby supporting the inclusion of all as being more comprehensively truly a part of the Philippines. The Mathematics Framework for Philippine Basic Education (MATHTED and SEI, in press), a document that aims to guide the development of curricular contents in mathematics, identifies cultural-rootedness as one of the cognitive values that mathematics education in the Philippines must inculcate. Cultural-rootedness is defined as ?appreciating the cultural value of mathematics and its origins in many cultures, its rich history and how it has grown and continues to evolve?. Ethnomathematics, described as the ?mathematics which is practiced among identifiable cultural groups, such as national tribal societies, labor groups, children of a certain age bracket, professional classes and so on? (D?Ambrosio, 1997, p.16), has rich potentials in increasing a country?s capacity to provide better mathematics education to its people. It is a vehicle for developing the value of cultural-rootedness thus recognizing and valuing the significant mathematical knowledge within the Philippines and how this mathematics has and continues to play a significant role in building capacity within the Philippines and its people. This paper provides examples of ?latent? mathematics that are found in various cultural groups in the Philippines. With these examples, the paper argues for changes in Philippine mathematics education to recognize and include Ethnomathematics encouraging teachers and communities to actively seek ways to include the non-traditional, non-Western mathematics in their teaching of mathematics in schools. These would include the different ways of counting, measuring, patterning, navigating, constructing, creating shapes, computing and other mathematical skills of various cultural groups. By this, Filipino students will learn to both appreciate the many cultures in the country and develop ways to include these cultures into the mainstream Philippine culture, thereby supporting the inclusion of all as being more comprehensively truly a part of the Philippines.